Streptococcus mutans Membrane Vesicles Harboring Glucosyltransferases Augment Candida albicans Biofilm Development - Wu, Ruixue; Tao, Ye; Cao, Yina; Zhou, Yan; Lin, Huancai (Frontiers in Microbiology, 2020)
Candida albicans, as the most common fungus in the oral cavity, is often detected in early childhood caries. Streptococcus mutans is the major etiological agent of dental caries, but the role of S. mutans on C. albicans growth and biofilm development remains to be elucidated. Membrane vesicles (MVs) are a cell-secreted subcellular fraction that play an important role in intercellular communication and disease progression. In the present study, we investigated whether MVs from S. mutans augment C. albicans growth and biofilm development. The results indicated that S. mutans MVs augmented C. albicans biofilm development but had no significant effect on C. albicans growth under planktonic conditions. Subsequently, we labeled S. mutans MVs with PKH26 and used confocal laser scanning microscopy (CLSM) to track S. mutans MVs, which were observed to be located in the C. albicans biofilm extracellular matrix. Monosaccharide tests showed that S. mutans MVs contribute to sucrose metabolism in C. albicans. Polysaccharides were significantly enriched in the S. mutans MV-treated group. MVs from ΔgtfBC mutant strains were compared with those from the wild-type S. mutans. The results revealed that MVs from the ΔgtfBC mutant had no effect on C. albicans biofilm formation and exopolysaccharide production. In addition, C. albicans biofilm transcriptional regulators (Ndt80, Als1, Mnn9, Van1, Pmr1, Gca1 and Big1) expression were upregulated in S. mutans MV-treated group. In summary, the results of the present study showed that S. mutans MVs harboring glucosyltransferases involved in exopolysaccharide production augment C. albicans biofilm development, revealing a key role for S. mutans MVs in cross-kingdom interactions between S. mutans and C. albicans.